Fabrication, Investigation and Characterization of Developed Microwave Processed Copper-Based Composite Castings - Bashir, Khalid (2026)
Electrical contact wires are essential parts of electrical devices, switches, relays, connectors, and power transmission and distribution systems. Their primary function is to create a consistent pathway for current to pass between two conductive surfaces so that electrical energy can be carried continuously. They are critical in electric railway lines because of their capacity to maintain high conductivity and low resistance, which reduces energy losses and prevents the generation of excessive heat. In electric railway lines, contact points provide a life span and reliability to the conducting wires and reduce the need for regular replacement or maintenance. The new technology needs to be evolved for different types of materials, including fibre-reinforced plastics, metal matrix composites, ceramics, and alloys, to enhance the lifespan. Because even little disturbances at contact points affect the efficiency, stability, resilience, and conductivity and resulting in failure of these wires. The development of sustainable, green, and energy-efficient processing techniques is the main focus of the current situation. Since alternative processing techniques and processes can overcome or mitigate the drawbacks of conventional methods, researchers must look into them. It is expected that the discovered methods will be extremely energy efficient, reduce emissions of CO2 or other undesirable hazardous gases, and yield higher-quality goods at a reasonable processing cost. In the present work, microwave energy is utilised for the melting and casting of powdered metal composites. The domestic microwave oven working at 2.45 GHz and 900 W maximum power is used as a microwave applicator. Microwave hybrid heating was used with charcoal as a susceptor material for melting the W-Mo metal powder particles. For the development of various MMCs, pure copper (Cu) powder was selected as the matrix material, which is approximately 99.53% pure. The reinforcements of Tungsten (W) and Molybdenum (Mo), approximately 99.45% and 99.30% pure, were selected. The matrix and reinforcement powders were premixed in a mechanical mixer to obtain homogeneously mixed powders, with reinforcement weight fractions of 5%, 10% and 15%. The premixed powder was preheated to 200°C and placed in the alumina cavity, which is exposed to microwave radiation for optimum processing times. The alumina cavity was used to cool under atmospheric conditions for the solidification of the castings. The developed castings were characterised using various relevant techniques to study the X-ray diffraction patterns (phase analysis), microstructural characterizations (using optical microscope and scanning electron microscope equipped with EDS), mechanical properties (Vickers’s microhardness, density, tensile strength and percent elongation, Grain size), functional characteristics (high temperature sliding wear behaviour) and high temperature electrical conductivity of cast samples. Microstructure of the developed copper cast, which reveals a regular, approximate hexagonal structure that resembles cellular growth during solidification. This type of solidification growth pattern is one of the peculiar characteristics (volumetric) of microwave heating and causes the least temperature gradient. The EDS analysis of microwave-cast pure Cu casting confirms the dominant element of Cu as the main component and some minor elements, including oxygen. Cu - x (5-15 %) W, where x = 5%, 10%, 15% W, casts revealed the presence of Cu and W as the main elements, with some minor peaks of oxygen. While in Cu - x (Mo) where x= (5-15%) Mo casts, x = 5%, 10%, 15% Mo confirms the Cu and Mo as the main elements and some minor peak of oxygen. The XRD pattern of pure copper casting clearly demonstrates copper's presence as an important constituent; however, the presence of the copper oxide phase has also been confirmed. In the Cu-x (5-15 wt.%) W composite castings, the phase peaks display a consistent pattern. The XRD patterns indicate the formation of Cu64O and CuWO4 phases at various positions. The Cu-x (5-15) wt. % Mo composite castings exhibit peak patterns that are highly consistent across all samples. The XRD patterns reveal the formation of Cu64O, Cu6Mo5O18, and MoO2 phases at various positions. All these intermetallic were favoured due to the thermal degradation of reinforcements at higher temperatures. The maximum level of porosity development in microwave-processed castings was 1.11 ± 0.41%, in Cu-5% Mo composite casting and the minimum porosity of 0.65% ± 0.09% for pure Cu castings. The lowest tensile strength was found in microwave processed pure Cu, i.e., 184 ± 2 MPa, while the highest tensile strength was found in Cu-15% W I, e, 301 ± 15.05 MPa with 20 ± 1% elongations. By adding the reinforcements, the load-carrying capacity increased, but hard phases of reinforcement restricted the plastic deformations, thus producing lower elongations. The density of the copper was found to be 87.5 %. with increased reinforcement. Cu-15%W shows the highest density, 98.71%. The Vickers’s microhardness of the microwave cast pure Cu was found to be 61.78 ± 3.08 Hv, while Cu-15% W showed 147.23 ± 7.36 Hv, which is 2.41 times higher than that of microwave processed pure Cu. The average grain size of commercially cast copper was found to be 38.02 ± 2.02. Significant grain refinement was observed in pure Cu, with an average grain size of 27.35 ± 1.36. With the addition of hard reinforcements, Mo and W, further refinement occurred, and the average grain size was reduced to 14.28 ± 0.70 for the Cu-15% Mo composite and 11.29 ± 0.56 for the Cu-15%W composite. The Functional characterization (in terms of pin-on-disc high-temperature wear tests), when exposed to a load of 2 kg, a sliding distance of 1000 m, and a sliding speed of 0.5 m/s, Cu-15%W and Cu-15%Mo composite castings demonstrated the least amount of cumulative weight loss. The minimum wear values were found to be 23.6 mg and 21.67 mg, respectively. However, at a sliding speed of 1.5 m/s and a load of 4 kg, pure copper shows the maximum weight loss, 66.4 mg, over 3000 m. The wear behaviour of Cu-Mo and Cu-W composite castings was significantly affected by changes in normal load, sliding speed, and reinforcement content. An increase in reinforcement content led to a prominent decrease in wear loss. Cu-10% Fe-15% Mo and Cu-10% Fe-15% W dual-reinforced composites are more resistant to wear than their single-reinforced and unreinforced counterparts, primarily due to better bonding, uniform reinforcement distribution, and the formation of stable tribo-oxide layers. For all composites, the coefficient of friction (COF) decreased with increasing sliding speed and load, most likely due to tribolayer formation and thermal softening. Cu-15%W exhibited the lowest COF (~0.25). The high-temperature electrical conductivity behaviour of pure copper and Cu–Mo/ Cu-W composites fabricated through microwave casting over the temperature range of 50-400°C. Pure copper exhibited the highest conductivity, decreasing from approximately 5.8 × 10⁷ S/m at 50°C to about 2.3 × 10⁷ S/m at 400°C due to enhanced electron–phonon scattering at elevated temperatures. The addition of 5-15 wt.% Mo and W led to a systematic decrease in conductivity across the entire temperature range, with Cu-15% composites showing the lowest values (≈1.4 × 10⁷ S/m at 400°C). This reduction is attributed to solute-atom, interfacial, and grain-boundary scattering effects introduced by the reinforcements. Despite the decline in electrical performance, the composites exhibited superior thermal stability and structural integrity at high temperatures. The overall results demonstrate that microwave energy is an effective technique for the melting and casting of pure Cu and Cu-based metal-matrix composites (CMMCs). The developed Cu-15 wt.% W composite exhibits significantly enhanced mechanical properties compared with pure Cu, including an increase of approximately 84% in microhardness, 64% in tensile strength, 13% in density, and about 66.5% improvement in tribological performance. These improvements are highly beneficial for extending the service life of electrical contact wires operating under sliding and impact conditions. Although the addition of tungsten leads to a reduction in electrical conductivity of approximately 74% lower than that of pure Cu, the composite still maintains sufficient current-carrying capability. Therefore, Cu-15 wt.% W can be considered a promising material for durable and energy-efficient electrical contact wire applications.
Keywords: Microwave hybrid heating; Microwave Casting; Mechanical Characterization; High temperature; Wear; High temperature Electrical Properties